Antwone Fisher [videorecording (DVD)] - Washington, Denzel, 1954-; Washington, Denzel, 1954-; Washington, Denzel, 1954-; Fisher, Antwone Quenton; Luke, Derek, 1974-; Bryant, Joy, 1976-; Richardson-Whitfield, Salli, 1967-; Davis, Viola, 1965- (20th Century Fox Home Entertainment, 2003)
Antwone Fisher, 25, is a gentle, soft-spoken seaman in the Navy. Unless he feels he's been disrespected--which prompts furious, violent outbursts that put him on the brink of a dishonorable discharge. Ordered to see a psychiatrist, eventually the story of his childhood in a foster home, where he was both beaten and sexually abused, comes out. Dr. Davenport argues that Antwone needs to deal with his past, find his family, and attain closure. For Antwone, the journey proves agonizing and freeing, as he puts his past behind him and graduates into responsible manhood.